PESANTREN’S ECONOMIC INDEPENDENCE DISCOURSE: REVITALIZATION OF FIKIH MUAMALAH LEARNING AS FINANCIAL LITERACY EDUCATION IN PESANTREN - Habib Maulana Maslahul Adi; Nur Romdlon Maslahul Adi; Afifah Ikram Mufidah (MASILE, 2023)
The function of pesantren is indeed as a place to gain religious knowledge (tafaqquh fi ad-dīn), but it cannot be denied that pesantren have great potential in the economy. Considering this potential, pesantren should prepare their cadres to become reliable and skilled resources in order to realize the economic independence of the pesantren. It is not enough for the development of santri resources to be equipped with entrepreneurship skills alone and without managerial skills, especially financial management skills. Therefore, santri need to obtain good financial literacy education so that they are competent in increasing the economic independence of the pesantren. This study aims to provide an overview of financial literacy education for santri in welcoming the economic independence of pesantren. As a conceptual scientific article, this study relies on exploration of various sources related to financial literacy and economic independence of pesantren. Based on the studies that have been conducted, it is concluded that financial literacy education for santri as an initial step towards the economic independence of pesantre can be carried out in three stages, namely: the introduction stage through the introduction of concepts and financial literacy material adapted to fiqh al-mu'āmalāt material; the application stage through extracurricular activities and khidmah in pesantren, and the development stage through programs to increase environmental involvement and pesantren collaboration with the community, leaders, institutions, and business actors.